Effects of strength training on functional capacity and health of the elderly: an integrative review (Research, Society and Development, 2021)
Objective: To identify the effects of strength training on the functional capacity and health of the elderly. Methodology: This is an integrative review study, which analyzed articles published from 2010 to 2020 in the Lilacs, SciElo and Pubmed databases, selected in an online search for exact descriptors and synonyms in Portuguese and English for the terms “strength training”, “functional physical capacity” and “elderly”. Full text articles available online, free of charge, in Portuguese, English or Spanish, published from 2010 to 2020, were included in order to obtain an updated context on the effects of strength training with the target audience of this study. The final sample consisted of 10 articles. Results: The data indicated that strength training at moderate or vigorous intensity provides benefits to the elderly through their own gain in muscle strength and improvement in aerobic capacity, which reduce the risk of falls, in addition to reducing blood pressure and depressive symptoms, whether in healthy elderly or with comorbidities. Final Considerations: Through this review, it was noticed that strength training improves the functional physical capacity of the elderly and favors healthy aging, as it reduces the risk of falls and contributes to the control of chronic diseases.